Magnetospheric research with advanced techniques : proceedings of the 9th COSPAR Colloquium held in Beijing, China, 15-19 April, 1996 - Lui, Anthony T. Y.; Xu, R. L. (Ronglan L.) (COSPAR colloquia series, 1998)
Launches of several major magnetospheric research satellites (i.e., Polar, Wind, and Interball) set the scene for extensive multi-platform investigations of the Earth's plasma environment in the era of the International Solar-Terrestrial Physics Program. Exciting new results from this Program and the ongoing innovative advances to scientific instrumentation and spacecraft technology are vitally important for the international space community in preparing for future plans in the upcoming new millenium. This volume is a product of the COSPAR Colloquium held in Beijing on April 15-19, 1996 aimed to consolidate these achievements. It contains state-of-the-art articles in the four areas of modern magnetospheric techniques, namely, (1) active experiment in space, (2) innovative measurement technique, (3) multi-point observation, and (4) numerical simulation and theoretical analysis. Researchers in the space community, both novices and experts, are expected to benefit from this collection of articles.